Potential Antioxidant Role of Tridham in Managing Oxidative Stress against Aflatoxin-B1-Induced Experimental Hepatocellular Carcinoma - Vijaya Ravinayagam; Ravindran Jaganathan; Sachdanandam Panchanadham; Shanthi Palanivelu (International Journal of Hepatology)
Hepatocellular carcinoma (HCC) is one of the most fatal cancers due to delayed diagnosis and lack of effective treatment options. Significant exposure to Aflatoxin B1 (AFB1), a potent hepatotoxic and hepatocarcinogenic mycotoxin, plays a major role in liver carcinogenesis through oxidative tissue damage and p53 mutation. The present study emphasizes the anticarcinogenic effect of Tridham (TD), a polyherbal traditional medicine, on AFB1-induced HCC in male Wistar rats. AFB1-administered HCC-bearing rats (Group II) showed increased levels of lipid peroxides (LPOs), thiobarbituric acid substances (TBARs), and protein carbonyls (PCOs) and decreased levels of enzymic and nonenzymic antioxidants when compared to control animals (Group I). Administration of TD orally (300 mg/kg body weight/day) for 45 days to HCC-bearing animals (Group III) significantly reduced the tissue damage accompanied by restoration of the levels of antioxidants. Histological observation confirmed the induction of tumour in Group II animals and complete regression of tumour in Group III animals. This study highlights the potent antioxidant properties of TD which contribute to its therapeutic effect in AFB1-induced HCC in rats.